Development of a New Type of Rehabilitation Mechanism for Bilateral Wrist Joint Training - Han Lisheng; Liu Zhifei; Li Lina; Huang Jiahai (Jixie chuandong, 2023)
A bilateral wrist joint training and rehabilitation mechanism is designed to meet the requirements of bilateral passive training better than unilateral active training. The rehabilitation mechanism adopts two spatial reverse double crank parallel sub mechanisms. The forward kinematics of the mechanism is analyzed in the spherical coordinate system, and the motion relationship of the two platforms is obtained. The Euler angles of the rolling, pitching and virtual yaw motions of the two platforms are measured, and the front and back muscles are measured simultaneously in the three motion modes. The experimental data shows that when the mechanism is rolling, the angular displacements of both platforms are equal in magnitude and opposite in direction, while the mechanism is pitching, the angular displacements of both platforms are the same in magnitude and direction. The maximum and average electromyography （EMG） values of anterior and posterior muscles measured during the bilateral active training are 319.65 mV and 352.2 mV higher than those measured during the resting state, and 155.9 mV and 184 mV higher than those measured during the unilateral passive training, respectively. The above results show that the developed bilateral training machine has mirror symmetry, can play a training effect on the wrist joint, and the training effect is better than that of the unilateral training.